2010
DOI: 10.1364/oe.18.027827
|View full text |Cite
|
Sign up to set email alerts
|

Coherent addition of fiber-amplified ultrashort laser pulses

Abstract: We report on a novel approach of performance scaling of ultra-fast lasers by means of coherent combination. Pulses from a single mode-locked laser are distributed to a number of spatially separated fiber amplifiers and coherently combined after amplification. Splitting and combination is achieved by polarization cubes, i.e. the approach bases on polarization combining. A Hänsch-Couillaud detector measures the polarization state at the output. The error signal (deviation from linear polarization) is used to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…The beam is finally focused by a spherical mirror at almost normal incidence, located in either the auxiliary chamber CH-01.03 for phase1 or in CH-01.04 for phase2. Assuming a laser peak intensity in the gas cell of the order of -10 W cm 15 2 results in estimated focal lengths of 2.2m (phase 1) and 5.7m (phase 2). The actual focal length to be used for the XUV generation will be determined during beamline commissioning.…”
Section: Detailed Layoutmentioning
confidence: 99%
“…The beam is finally focused by a spherical mirror at almost normal incidence, located in either the auxiliary chamber CH-01.03 for phase1 or in CH-01.04 for phase2. Assuming a laser peak intensity in the gas cell of the order of -10 W cm 15 2 results in estimated focal lengths of 2.2m (phase 1) and 5.7m (phase 2). The actual focal length to be used for the XUV generation will be determined during beamline commissioning.…”
Section: Detailed Layoutmentioning
confidence: 99%
“…Different elements have been successfully proposed such as partially reflective surfaces [9] or polarization dependent beam splitters [6]. While all of these elements can in principle just combine two beams, by cascading them, the number of channels to be combined can be increased.…”
Section: General Considerations On Coherent Beam Combining Of Ultrashmentioning
confidence: 99%
“…In the ultrashort pulse regime, coherent combination makes it possible to scale the pulse energy, as well as the average power independently from the amplification scheme. This concept has already been demonstrated for two single mode fiber amplifiers, delivering ultrashort pulses with a combining efficiency of over 95% [6]. Additionally, by using LMA fibers, combined pulse energies of 120µJ have been already achieved [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical work [1] has shown that the maximum peak power that can be extracted from a photonic crystal fibre (PCF) is of the order of 10 GW. So, to drive a wakefield, the output of many fibres need to be combined together [1,2,3]. A facility-scale, coherently-combined fibre-laser system, utilising potentially hundreds of PCFs, will generate significant cost.…”
Section: Introductionmentioning
confidence: 99%